A golden thread, a presence amongst uniforms, and a good deal of data: studying public confidence in the London Metropolitan Police - Stanko, B; Jackson, J; Bradford, B; Hohl, K (2012)
This article discusses how four authors came together to create - inside a police service - a specific approach to public 'trust and confidence'. We have had many theoretical debates - about the nature of public understanding of policing, police culture, procedural justice and public trust in public institutions in a democracy. Also, while we continue to debate, we wade through mounds of data gathered routinely through the Metropolitan Police's own Public Attitude Survey. Reporting internally on a quarterly basis, the survey challenges police colleagues to think about how the police must demonstrate to citizens their trustworthiness to act fairly, effectively and with the best interests of communities at heart. Our experience of moulding the discourse about public confidence inside the largest police service in the UK suggests that police culture itself has been challenged by the accountability that lies at the heart of trust and trustworthiness. We have been asked by the editors of this issue to share with readers how we have come to create a contribution to understanding what drives confidence in policing, which is now a routine part of its performance management. © 2012 Copyright Taylor and Francis Group, LLC.